2019
DOI: 10.12927/hcq.2019.26024
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences in Canadian Hospitals

Abstract: With its first release of patient experience data, the Canadian Institute for Health Information provides a high-level summary of results from the Canadian Patient Experiences Survey-Inpatient Care captured in the Canadian Patient Experiences Reporting System. It examines how Canadian patients feel about how information was communicated and shared at different stages of their hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
2
12
1
Order By: Relevance
“…Previous studies have demonstrated the role between high quality care transitions and post-discharge outcomes [1,3,9,12,23]. Interestingly, our study demonstrates higher patient experience scores than was reported in the only other cross-sectional study of patient experience across multiple Canadian provinces [20]. While some differences may be due to our focus on discharge management rather than patient satisfaction which was included in this study, our results likely represent the increasing attention on care transition quality and hospital-specific initiatives that are underway in Ontario [16].…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Previous studies have demonstrated the role between high quality care transitions and post-discharge outcomes [1,3,9,12,23]. Interestingly, our study demonstrates higher patient experience scores than was reported in the only other cross-sectional study of patient experience across multiple Canadian provinces [20]. While some differences may be due to our focus on discharge management rather than patient satisfaction which was included in this study, our results likely represent the increasing attention on care transition quality and hospital-specific initiatives that are underway in Ontario [16].…”
Section: Discussionsupporting
confidence: 40%
“…Improving patient experience during care transitions from hospital to home has gained much attention over the last 10 years [4][5][6][7][8][9]. However, Canada has only focused on capturing patient experience recently [10,14,[17][18][19][20]. Our study provides a deeper dive into areas for system improvement at a time when care coordination and communication practices were likely further hindered due to the COVID-19 pandemic [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest several implications for policy, practice and ongoing research. Given widespread need to improve the quality of hospital care [2][3][4][5], and global attention on PE as a means of doing so [6][7][8], these implications are broadly relevant. Healthcare policymakers, hospital executives and PE managers may identify PE infrastructure or processes that hospitals lack to inform resource allocation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients who gave high overall ratings of their hospital ranged from 35 to 60% across 13 countries [4]. In Canada, a survey of over 90,000 Canadians discharged from more than 300 acute care hospitals in 5 provinces between 2015 and 2018, 54% said their medication was always wellexplained, 56% felt their care was always well-coordinated by hospital staff, and 66% felt completely informed of their condition, treatment and medication upon discharge [5]. Clearly, there is a need to further improve hospital patient experiences and care.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a survey of hospital patients across 13 countries showed that overall quality ratings were low to moderate, ranging from 35 to 60% [ 2 ]. Another survey of 90,000 + patients hospitalized in Canada similarly revealed moderate views of the care they received: 56% reported that care was well-coordinated and 66% reported being well-informed about their condition and its management [ 3 ]. Given the imperative to improve patient experiences and outcomes in a cost-efficient manner, strategies are needed to support quality improvement efforts in hospitals.…”
Section: Introductionmentioning
confidence: 99%